Sovereignty and the diffusion of political authority in multinational and transnational governance - Held, David (Faculdade de Filosofia e Ciências, 2014)
This article looks at the change, after World War II, in the structure of world power. Such a structural transformation brought consequences for the pattern of postwar global political and security relations. Therefore, will be analyzed how the states became wrapped in an array of global governance systems and arrangements, impacting on the concept assigned to sovereignty. Resumo: Esse artigo analisa a mudança, após a Segunda Guerra Mundial, na estrutura do poder mundial. Tal mudança estrutural trouxe consequências para o padrão de relações políticas e de segurança globais do pós-guerra. Nesta perspectiva, será analisado como os Estados envolveram-se em uma variedade de sistemas de governança global e arranjos, impactando no conceito atribuído a soberania.